An improved noninvasive method for measuring heartbeat of intertidal animals. (28th February 2013) - Burnett, Nicholas P.; Seabra, Rui; de Pirro, Maurizio; Wethey, David S.; Woodin, Sarah A.; Helmuth, Brian; Zippay, Mackenzie L.; Sarà, Gianluca; Monaco, Cristián; Lima, Fernando P.
<x xml:space="preserve">Abstract</x> Since its emergence two decades ago, the use of infrared technology for noninvasively measuring the heartbeat rates of invertebrates has provided valuable insight into the physiology and ecology of intertidal organisms. During that time period, the hardware needed for this method has been adapted to currently available electronic components, making the original published description obsolete. This article reviews the history of heartbeat sensing technology, and describes the design and function of a modern and simplified infrared heartbeat rate sensing system compatible with many intertidal and marine invertebrates. This technique overcomes drawbacks and obstacles encountered with previous methods of heartbeat rate measurement, and due to the sensor's small size, versatility, and noninvasive nature, it creates new possibilities for studies across a wide range of organismal types.